Coronavirus disease 2019 (COVID-19): Multisystem review of pathophysiology. (September 2021) - Mir, Tanveer; Almas, Talal; Kaur, Jasmeet; Faisaluddin, Mohammed; Song, David; Ullah, Waqas; Mamtani, Sahil; Rauf, Hiba; Yadav, Sunita; Latchana, Sharaad; Michaelson, Nara Miriam; Connerney, Michael; et al.
Abstract: Coronavirus disease-19 (COVID-19) pandemic is associated with high morbidity and mortality. COVID-19, which is caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS CoV-2), affects multiple organ systems through a myriad of mechanisms. Afflicted patients present with a vast constellation of symptoms, from asymptomatic disease to life-threatening complications. The most common manifestations pertain to mild pulmonary symptoms, which can progress to respiratory distress syndrome and venous thromboembolism. However, in patients with renal failure, life-threatening cardiac abnormalities can ensue. Various mechanisms such as viral entry through Angiotensin receptor (ACE) affecting multiple organs and thus releasing pro-inflammatory markers have been postulated. Nevertheless, the predictors of various presentations in the affected population remain elusive. An ameliorated understanding of the pathology and pathogenesis of the viral infection has led to the development of variable treatment options, with many more that are presently under trial. This review article discusses the pathogenesis of multiple organ involvement secondary to COVID-19 infection in infected patients. Highlights: This review sheds light on the pathogenesis of multi-organ involvement secondary to COVID-19 infection. The predictors of various presentations in the affected population are not clear at present. A better understanding of the pathology and pathogenesis of the viral infection will be pivotal in the development of variable treatment options. Various proposed mechanisms such as viral entry through Angiotensin receptor (ACE) affecting multiple organs, releasing pro-inflammatory markers and cytokines inducing hypercoagulable state and cytokine storm syndrome have been postulated.